Case studies and guidelines for energy efficient communities. A guidebook on successful urban energy planning. - (:unkn) unknown (Fraunhofer IRB Verl., 2013)
What are the barriers that prevent us from achieving our long-term energy goals in cities or, more generally, in our built environment? What can be learned from successful Case Studies in neighborhoods, districts or cities? Is there any economically viable way to apply these advancements to whole cities? This Annex 51 wants to provide such answers, based on the evaluation of over 20 Case Studies carried out within the 11 participating countries and elaborated in the form of this guidebook on successful local energy planning. In eight chapters and several detailed attachments a manual to derive municipal energy master plans for towns or cities on one hand, and local neighborhood energy plans on the other is presented, which serves as a guideline for municipal decision makers, real estate developers and urban planners as well.
Keywords: Energie; Energieversorgung; Quartiersplanung; Gemeinde; Stadtquartier; Energieeinsparung; Technologie; Effektivität; Fallstudie; Energieeffizienz; Klimaschutz; Dezentrale Energieversorgung; Energieberatung